Holistic redemptive pastoral ministry in the fragmented transit hall of existence - Meylahn, Johann-Albrecht (HTS teologiese studies, 2010)
The grand narratives have all but gone – what is left are numerous narratives, each addressing a certain aspect of our lives; there is a different narrative for our professional lives, another for our family lives, for our social lives and yet another for our spiritual lives. We find ourselves in this ‘transit hall’, forever changing flights or trains, depending on which narrative sphere we are entering or leaving. In each narrative we take on a different character, defined and shaped by the specificities of that narrative. Thus, ‘transition’ in the sense of change can no longer be understood as only linear, but as constant and multidimensional. With the use of Lacan’s discourse theory, this fragmented existence will be unpacked and a redemptive alternative sought.This paper is an attempt to address this multi-narrative existence without imposing yet another grand narrative. Thus it focuses on offering a narrative space that is, (1) holistic, in the sense that it addresses all the different narratives, (2) pastoral, in that it addresses the person and (3) redemptive, in that it offers something new, meaningful and hopeful. Such a narrative space moves the church from its ‘ghetto mindset’, where traditions and values are maintained, to being fully open and vulnerable to the present reality, whilst yearning for the Messianic to reveal an alternative future.